OPENING NEW EDUCATIONAL FIELDS: Towards the Education in Adults - García Mínguez, Jesús (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2011)
The idea of education throughout life, certain and extended, is an advance that encompasses everyone independently on his age. This article invites to push the educational impulses to the elderly people, as a way to catch the continuity of qualifiedly personal and social life. To support this statement, the author goes into the concept of education as a right recognized by the ONU in 1948. Likewise he observes its historic evolution to where it becomes a usually assumed phenomenon.